Cultures and settlements - Miles, Malcolm, 1950 June 6-; Kirkham, Nicola (Advances in art & urban futures, 2003)
This volume considers the making of settlement as a process of identity formation. Taking the position that a culture signifies a way of life, it asks how cultural frameworks inform patterns of settlement, and how the built environment, as process and design, conditions cultural production and reception. The disciplinary fields this intersects include architecture, urban design, sociology, cultural and human geography, cultural studies and critical theory. Contributors work in a range of such fields, in Europe and Latin America.